PEMETAAN KONDISI RANTAI PASOK BELIMBING KOTA DEPOK, PROPINSI JAWA BARAT - Anna Rahmawati; Nunuk Adiarni; Zulmaneri (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Depok’s Star fruit has many advantages rising to high demands that have not been fully met. These advantages need to be optimized to increase competitiveness by maintaining fruit quality along the supply chain through the implementation of Good Logistic Practices (GLP). The implementation of GLP requires resources, capabilities and needs of each business actor along the supply chain. Considering the capacity and capabilities of star fruit business actors in Depok City, most of whom are micro and small-scale entrepreneurs, the implementation of standards will face difficulties.  In this case, an active initiatives is needed from the government and associations to create programs and regulations that can improve the capabilities of star fruit agribusiness actors. This study aims to ensure the readiness of the star fruit supply chain in Depok City in implementing Good Logistic Practices (GLP) starting from mapping the supply chain conditions. The study is qualitative using the Food Supply Chain Network (FSCN) analysis framework from Van der Voorst. The results of the study found that there were 6 supply chain patterns formed in an effort to deliver star fruit from Depok City to consumers. In addition, this research also describes in detail the targets, management, structure, business processes and resources used in the supply chain.